Kui Hign Kui (estrella atada a estrella) - Plataforma de transformación e interacción para plantas ancestrales (2020)
The plan aims to impact the areas affected by violence with the biggest coca crops, fostering economy in vulnerable territories, generating alternatives based on the coca leaf and dignifying the coca workers and segregated population. It’s planned to unify those places with a 12 km lineal park that will host more than 200 endangered and 50 native tree species that are not found anywhere else in the country. This park will be connected through cable cars, terrestrial ways, and river links. It will have a station succession, camping areas, security equipment, and ports; reaching 10 hectares distributed in three cores, ready to supply needs and provide jobs for over 5.000 people.